About the Influence of Doping Approach on the Alkali Metal Catalyzed Slow Pyrolysis of Xylan - Valentina Gargiulo; Paola Giudicianni; Michela Alfè; Raffaele Ragucci (Journal of Chemistry)
In this study, we highlighted how the catalytic effect of alkali metals on xylan pyrolysis is strongly affected by the adopted doping approach. Thermogravimetric and pyrolysis tests, up to 973 K and at a heating rate of 7 K/min, were conducted on a set of potassium- or sodium-doped xylan samples containing controlled amounts of KCl or NaCl introduced, starting from a demineralized xylan sample, through a conventional wet impregnation approach. Pyrolysis product yields from xylan-doped samples were compared with those related to the demineralized xylan sample. The performances of the doping procedure were assessed through a comparison with the data collected on raw xylan and a xylan sample doped with potassium ions by a cationic exchange approach. The results showed that the introduction of potassium ions by wet impregnation using a chloride salt negligibly affected the pyrolytic behaviour of the demineralized sample and indicated that the doping approach based on wet impregnation using chloride salts is not appropriate for the study of the effect of alkali metals on the pyrolysis of polysaccharides bearing acidic functional groups as xylan.